Prática De Planejamento Escolar Na Rede Estadual Paulista De Ensino: Plano De Ação Participativo Para Escolas (Pap) - Paula, Daniela Aparecida Guedes De [UNIFESP] (2017)
The Participatory Action Plan (PAP) was a support instrument for school planning and management elaborated by São Paulo State Educational Secretary (Secretaria de Educação do Estado de Sao Paulo) in partnership with Sao Paulo State Public Administration Secretary (Secretaria de Gestão Pública do Estado de São Paulo), implemented in the public school system in 2012. This research was focused mainly on the induction and execution of this planning practice in the school management of priority schools. The general objective was to investigate how the school principals and also how the educational supervisors who were involved in this experiment evaluated the induction and local execution of this policy, characterized as a policy to strengthen planning and school management. As specific objectives, I sought to examine the methodology that was used in the induction and local implemention of the Participatory Action Plan (PAP); to describe the interaction that the Principals of Priority schools and Educational Supervisors had with the school planning and management instrument; to investigate the knowledge of the process of strategic and participatory planning, particularly highlighting the Participatory Action Plan (PAP) implemented in the year of 2012 and analyze,from the point of view of the Educational Supervisors and the Public School Principals of the Teaching Board of Jacareí-SP Region, what were in fact the difficulties of understanding and formal implementation of this planning and management tool. The research was developed under the qualitative approach and systematic procedures of data collection were adopted through interviews with those School Principals and Educational Supervisors. The documentary analysis included tutorials that expressed this policy and planning documents, published by São Paulo State Educational Secretary (Secretaria de Educação do Estado de São Paulo- SEESP). The Participatory Action Plan (PAP) was the expression of school-centered management, because it was up to the schools to make a diagnosis of the problems under their governance and to build a Plan to overcome them.This model, which consisted of the strategy of decentralizing local school decision making, involved preferably the whole school community, cause displeasure to School Principals and Educational Supervisors because they recognized that the main problems that were affecting the schools were not the ones under their governance.This movement of descentralization caused substantial disquiet in the school routine, showing that is management, and not quality of education, is the object of educational policy. The level os participation announced in the text and the level of participation actually achieved through the induction made by the scheadule prescribed by São Paulo State Educational Secretary (Secretaria de Educação do Estado de São Paulo- SEESP) were not in line. As a synthesis of the results, the analysis of the data allowed to affirm that the methodology of strategic planning, postulated by the Participatory Action Plan (PAP) was not incorporated into the planning practice, since the lack of and exogenous monitoring to the Teaching Board of Jacareí-SP Region and to the schools was pointed out as an essential element for the continuity os the Plan, due to the lack of links with the policy conceived by São Paulo State Educational Secretary (Secretaria de Educação do Estado de São Paulo- SEESP).The absence of belonging to educational policies weakened the ability of protagonists and continuity of the Project, subjecting schools to the circunstantial winds of initiatives of the central organs of São Paulo State Educational Secretary (Secretaria de Educação do Estado de São Paulo- SEESP)